Complete genome analysis of highly pathogenic bovine ephemeral fever virus isolated in Turkey in 2012 - Abayli, Hasan; Tonbak, Sukru; Azkur, Ahmet Kursat; Bulut, Hakan (Springer Wien, 2017)
Relatively high prevalence and mortality rates of bovine ephemeral fever (BEF) have been reported in recent epidemics in some countries, including Turkey, when compared with previous outbreaks. A limited number of complete genome sequences of BEF virus (BEFV) are available in the GenBank Database. In this study, the complete genome of highly pathogenic BEFV isolated during an outbreak in Turkey in 2012 was analyzed for genetic characterization. The complete genome of the Turkish BEFV isolate was amplified by reverse transcription-polymerase chain reaction (RT-PCR) and sequenced. It was found that the complete genome of the Turkish BEFV isolate was 14,901 nt in length. The complete genome sequence obtained from the study showed 91-92% identity at nucleotide level to Australian (BB7721) and Chinese (Bovine/China/Henan1/2012) BEFV isolates. Phylogenetic analysis of the glycoprotein gene of the Turkish BEFV isolate also showed that Turkish isolates were closely related to Israeli isolates. Because of the limited number of complete BEFV genome sequences, the results from this study will be useful for understanding the global molecular epidemiology and geodynamics of BEF.
Keywords: Experimental-Infection